2017
DOI: 10.1016/j.fcr.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Root traits confer grain yield advantages under terminal drought in chickpea ( Cicer arietinum L.)

Abstract: HighlightsRoot system development transcribed the drought yields of chickpea genotypes.In response to drought, roots turned more prolific, thinner & penetrated deeper soils.Highest drought tolerance depended on the strength of reproductive-phase root system.RLD after 45 DAS & deep RDW before maturity & early pod-fill RSR contributed to DS.Tolerance relied on maximum water acquisition enhancing shoot biomass & partitioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 83 publications
(155 reference statements)
2
60
0
Order By: Relevance
“…In order to elucidate the role of root traits contributing in grain yield, Gaur et al (2008) showed higher RLD and maximum root depth (RDp) in shallow soil could assist in increasing seed yield under drought stress. Likewise, Ramamoorthy et al (2017) also evidenced positive association of RLD and grain yield under drought stress in chickpea. However, positive association of root traits with grain yield under drought stress remains inconsistent across various environment (Zaman-Allah et al, 2011b), leading plant breeders reluctant to use this trait in breeding program for drought tolerance.…”
Section: Role Of Root Traits Contributing Drought Adaptationmentioning
confidence: 73%
“…In order to elucidate the role of root traits contributing in grain yield, Gaur et al (2008) showed higher RLD and maximum root depth (RDp) in shallow soil could assist in increasing seed yield under drought stress. Likewise, Ramamoorthy et al (2017) also evidenced positive association of RLD and grain yield under drought stress in chickpea. However, positive association of root traits with grain yield under drought stress remains inconsistent across various environment (Zaman-Allah et al, 2011b), leading plant breeders reluctant to use this trait in breeding program for drought tolerance.…”
Section: Role Of Root Traits Contributing Drought Adaptationmentioning
confidence: 73%
“…Lata et al, (2017) have also observed a decrease in plant biomass with increasing concentrations of NaCl alongwith Boron. Modification to root system architecture may improve desirable agronomic traits in chickpea such as yield, drought tolerance and resistance to coarse soil texture as well as nutrient deficiencies (Chen et al, 2016;Ramamoorthy et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Our research demonstrates selected endophytes increase root and shoot under drought conditions, which is similar to results on other crops (Mattos et al., ). Modification to root system architecture may improve desirable agronomic traits in chickpea such as yield, drought tolerance and resistance to coarse soil texture as well as nutrient deficiencies (Chen, Ghanem, & Siddique, ; Ramamoorthy, Lakshmanan, Upadhyaya, & Vadez, ).…”
Section: Discussionmentioning
confidence: 99%